Space weathering on the lunar nearside and farside constrained from Si isotopes - Hui-Yan Zhang; Hui-Min Yu; Hao-Lan Tang; Yu-Chao Lin; Zicong Xiao; Lin Yang; Jin-Ting Kang; Ji Shen; Liping Qin; Fang Huang (Nature Communications)
Abstract Over long timescales, space weathering processes can modify the compositions of surface materials on the Moon. To assess the effects of space weathering of lunar soils, we study Si isotopes of Chang’E-5 (CE-5) and Chang’E-6 (CE-6) returned samples, and lunar meteorites. Here we show that both bulk soils from CE-5 and CE-6 exhibit heavier Si isotopic compositions than the basalt clasts within the soils and lunar meteorites, indicating that the space weathering obviously increase δ30Si of lunar soils. Furthermore, the CE-6 soil from the lunar farside has heavier Si isotopic values than the average of CE-5 soils from the nearside, suggesting that the CE-6 soil has experienced a higher space weathering degree than the CE-5 soils. This increased weathering degree could be attributed to either a longer weathering period or stronger micrometeorite impacts on CE-6 soil from farside compared to CE-5 soils from nearside.